LEARNING ENGLISH IN IMMERSIVE ENVIRONMENTS: A STUDENT-CENTRIC PERSPECTIVE AT KAMPUNG INGGRIS PARE - Ariya Agustin; M. Bambang Purwanto; Umar; Moch. Malik Firdaus (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
Learning English in an immersive environment is increasingly relevant to improving student competence in the era of globalization. This research highlights crucial issues related to the effectiveness of immersivebased learning in Kampung Inggris Pare, Kediri, East Java. The problem identified was the lack of an in-depth study of the relationship between students' perceptions and their learning outcomes in an environment that supports intensive use of English. This study explores students' perceptions of immersive-based learning and its impact on their speaking, listening, reading, and writing skills. Using a qualitative descriptive approach with a research sample of 50 students from the Domestic English course, data was obtained through in-depth interviews, observations, and documentation. The results showed a significant improvement in students' English skills, with an average increase in post-test scores of 25% compared to the pre-test. Thematic analysis reveals that facilities, programs, learning methods, and environments support active student engagement. The study concluded that the immersive environment contributed significantly to the effectiveness of English language learning